Evaluation of the Family Hope Program (PKH) in Taraitak Village, North Langowan District - Kiling, Ekleisia Kristi; Masengi, Evi Elvira; Kandou, Selphius (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This study aims to determine, describe and analyze the Evaluation of the Family Hope Program (PKH) in Taraitak Village, Langowan Utara District in accordance with the Regulation of the Minister of Social Affairs of the Republic of Indonesia Number 1 of 2018 concerning the Family Hope Program and the PKH Implementation Guidebook using qualitative research methods. The results showed that: 1) There are technical guidelines and rules that have been given by PKH administrators through the implementation of deliberations, but PKH policy actors still do not know in detail the guidelines and rules regarding PKH, then there are 36 KPM PKH in Taraitak Village but there is still no updating of KPM PKH data. 2) KPM PKH receives money sent to the accounts of each KPM and also receives basic necessities at BRI-Link Agents, but the recipients of PKH social assistance in Taraitak village are still not on target.  3) Existing village officials do not know the exact amount of funds received by KPM PKH, but this PKH policy is very useful and even helps the community economy.